Coarsening mechanism of LiAlO2 in acidic and basic molten carbonate salts. (September 2021) - Heo, Su Jeong; Hong, Junsung; Singh, Prabhakar
Graphical abstract: Highlights: The coarsening behavior of α-LiAlO2 in molten carbonate was studied under different p CO2 . The particle growth of LiAlO2 is accelerated with α–γ phase transition in low p CO2 . The crystal growth in basic melt conditions is dominated by Ostwald ripening. Oriented attachment growth occurs primarily on (003) plains. Abstract: Long-term corrosion behaviors of molten carbonate fuel cell (MCFC) electrolyte matrix with LiAlO2 particle coarsening are evaluated in eutectic Li-Na carbonate melts with different p CO2 . In low p CO2 (basic), the rapid growth of LiAlO2 particles by Ostwald ripening is observed. TEM analysis verifies the continued process of dissolution and precipitation of LiAlO2 nanocrystals that promotes LiAlO2 crystal growth. It is revealed that this growth process is accompanied by α–γ phase transition through a Li5 AlO4 intermediate phase. In high p CO2 (acidic) conditions, oriented attachment, primarily between the (003) and (012) planes of α-LiAlO2 crystals, leads to interparticle coalition and growth.